Penerapan Digital Marketing pada UMKM E&E Seafood di Baloi Kota Batam - Hesniati; Oktarianto, Eddy (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
E&E Seafood is a Micro, Small and Medium Enterprise (MSME) which operates in the sale of food and drinks, especially food with nuances of Chinese and Indonesian cuisine, located in Batam City. This MSME, which has been around for 3 years, has moved 3 times, so many customers have lost contact, and this has caused a decrease in turnover due to a decrease in food orders. The aim of this activity is to apply digital marketing using social media to E&E Seafood MSMEs to introduce them further to the public and increase sales turnover. The method used to overcome the problems that occur in E&E Seafood MSMEs is by carrying out digital marketing which carries out promotions related to food sold using the social media applications Instagram and Facebook. After carrying out this community service activity for 3 months, it can be concluded that the activities carried out smoothly are in accordance with the objectives of this activity. Where the author has carried out digital marketing promotions using Instagram and Facebook applications and producing a module to continue promotional activities for E&E Seafood MSMEs.